2010
DOI: 10.1016/j.juro.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Penile Dermal Flap in Patients With Peyronie's Disease: Long-Term Results

Abstract: Despite the attractiveness of the operation to our knowledge no other experience with this technique has been reported. Our results differ from those reported, although we tried to exactly follow the original technique of dermabrading the flap with sandpaper. Based on these results we abandoned the penile dermal flap in patients with Peyronie's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…[46][47][48] The reported patient satisfaction Larsen 29 rate with these procedures ranges from 41% to 96%, partner satisfaction has been reported at 77% and rigidity adequate for coitus reported from 79% to 100%. 22,46,[48][49][50][51] ED is reported in 0%-35% with a trend toward increased risk of ED in men over the age of 60 years, as well as a higher risk of ED when grafting is performed to correct ventral curvature. 22,48 Depending on the graft material used, recurrence of greater than 30u curvature can be seen from 0% to 16% with plaque incision/excision and grafting procedures.…”
Section: Tunical Lengthening Procedures (Incision or Partial Excisionmentioning
confidence: 99%
“…[46][47][48] The reported patient satisfaction Larsen 29 rate with these procedures ranges from 41% to 96%, partner satisfaction has been reported at 77% and rigidity adequate for coitus reported from 79% to 100%. 22,46,[48][49][50][51] ED is reported in 0%-35% with a trend toward increased risk of ED in men over the age of 60 years, as well as a higher risk of ED when grafting is performed to correct ventral curvature. 22,48 Depending on the graft material used, recurrence of greater than 30u curvature can be seen from 0% to 16% with plaque incision/excision and grafting procedures.…”
Section: Tunical Lengthening Procedures (Incision or Partial Excisionmentioning
confidence: 99%
“…These results are similar with those of other studies in which patients reported also low satisfaction rates after a long-term follow-up. 21,23,27 The relatively low satisfaction rates in the present study and other questionnaire-based studies also need to be judged under the perspective that such questionnaire-based studies tend to lead to significantly less positive results than direct interviews as reported by van der Horst et al…”
Section: Discussionmentioning
confidence: 57%
“…Even though some studies described excellent results after grafting procedures, 26,35 others reported, in accordance with our observations, a reduced erectile function of patients after a grafting procedure. 21,23,27 Hsu et al 26 reported equivalent erectile function after venous grafting procedures in comparison to the preoperative situation in patients with PD and with congenital deviation after an average follow-up of 43 months (7 month to 10 years), whereas Kim et al 27 described a significantly reduced erectile function/rigidity after a grafting procedure with venous patches after a medium follow-up time of at least 1 year compared to simpler shortening procedures. Also in line with the results of our study, Kim et al 27 described a higher loss of sensation in patients after grafting procedure than after ST procedures even though differences in our study were statistically not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex surgical procedures using grafts are often used in penile reconstructive surgery, presenting a wide range of success rates. This suggests that the ideal graft for hTA substitution is not yet available [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%